Features of the Design Thinking methods as a modern strategy of design in the context of environmental design - Safronova, O. (Theory and practice of design, 2017)
In the work was conducted a meaningful analysis of the strategy of DesignThinking in terms of its compliance with current trends in environmental design; novelty of methods that are used in it and the expediency of its introduction in the educational process. Analysis of all stages of the strategy has shown that it involves both new and improved known predesign analysis methods aimed at creating conditions for the disclosure of creativity of participants in project and meet the modern requirements with man-design approach.